Actions of the fall prevention protocol: mapping with the classification of nursing interventions - Vanessa Cristina Alves; Weslen Carlos Junior de Freitas; Jeferson Silva Ramos; Samantha Rodrigues Garbis Chagas; Cissa Azevedo; Luciana Regina Ferreira da Mata (Universidade de São Paulo, 2017)
ABSTRACT Objective: to analyze the correspondence between the actions contained in the fall prevention protocol of the Ministry of Health and the Nursing Interventions Classification (NIC) by a cross-mapping. Method: this is a descriptive study carried out in four stages: protocol survey, identification of NIC interventions related to nursing diagnosis, the risk of falls, cross-mapping, and validation of the mapping from the Delphi technique. Results: there were 51 actions identified in the protocol and 42 interventions in the NIC. Two rounds of mapping evaluation were carried out by the experts. There were 47 protocol actions corresponding to 25 NIC interventions. The NIC interventions that presented the highest correspondence with protocol actions were: fall prevention, environmental-safety control, and risk identification. Regarding the classification of similarity and comprehensiveness of the 47 actions of the protocol mapped, 44.7% were considered more detailed and specific than the NIC, 29.8% less specific than the NIC and 25.5% were classified as similar in significance to the NIC. Conclusion: most of the actions contained in the protocol are more specific and detailed, however, the NIC contemplates a greater diversity of interventions and may base a review of the protocol to increase actions related to falls prevention..